Modernization with Chinese Characteristics and Great Power - Hu, Angang (Understanding Xi Jinping's Governance,, 2023)
This open access book expounds in detail on the profound meaning and main characteristics of modernization with Chinese characteristics. This was done utilizing tools of historical investigation and fact-based research on the modernization of New China. The author provides a far-reaching outlook of the strategic goals and future trends of modernization with Chinese characteristics. In this book, the author answers the questions: What is modernization with Chinese characteristics? How did this modernization develop, and what are its main features? In what direction will it develop in the future? Why did China propose to basically realize the goal of socialist modernization by 2035? How can China achieve this ambitious goal on schedule? What major impact will this modernization have on China and the world? This book adheres to the concept of "knowledge for the people, knowledge for the country, and knowledge for mankind." It actively explores and summarizes the laws of modernization with Chinese characteristics and fully elucidates its characteristics. This book not only provides decision-makers with a basis for understanding national conditions and their national policy research, but also serves as an important reference for party members, cadres, and readers to understand the path of modernization with Chinese characteristics.